PENENTUAN LOKASI ALTERNATIF TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) MENGGUNAKAN QUANTITATIVE METHOD - Muhammad Zainuddin Fathoni (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Placement and determination of waste landfill locations in each city is very important. The location of a landfill that is not well organized will cause some negative consequences, which can cause damage to infrastructure; local environmental pollution; release of methane gas which is called organic decomposition; means of carrying diseases such as rats and flies; and simple interference. The existing landfill in Gresik city, precisely in the Ngipik Village, needs to be evaluated again because besides being in an urban location, the TPA has already been overloaded. Stakeholders need to find alternative locations to organize the city and make the city more comfortable for residential and urban areas. The solution to the problem requires a support method to find a solution. One method of supporting the decision is the method of transportation, this method can help to determine the optimal location of various alternatives. The transportation method discusses the distribution of goods from a number of sources (supply) to various destinations (requests) with the aim of minimizing the costs of transportation that occur. The results of calculating the optimal solution for each location using POM software by using a combination of existing landfill with TPA proposed I total costs spent in a day Rp.1.764.105,20. Temporary costs incurred using the existing landfill combination with TPA proposed II is Rp. 1.981.150,60. And the costs incurred using the existing landfill combination with the TPA proposed I and TPA proposed II ​​amounting to Rp.2.121.919,80. The combination of the use of the existing landfill with TPA proposed I has the lowest cost value of all alternatives.